PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN PADA SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Pemy Christiaan; Sri Meike Jusup; Rusdi Abdul Karim (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2023)
This study is intended to determine the effect of profitability and leverage on company value in the basic industrial and chemical sectors listed on the Indonesia Stock Exchange with the sample used being 22 companies in the Basic Industry and Chemical sectors listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. The profitability variable is measured using the Return On Asset ratio, the Leverage variable is measured using the Debt to Equity ratio while the company Value variable uses Price Book Value. The results of the study prove that partially Profitability and Leverage have a positive and significant effect on Company Value. This study also produced a coefficient of determination value of 26.9% which shows that this research model can explain that Company Value is influenced by 26.9% of the variables of this study and 73.1% is influenced by other variables that are not studied in this study.